The Analysis of the Spatial Stability of Prices on the Secondary Housing Market - Batóg, Barbara; Foryś, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The purpose of the paper is the spatial analysis of transaction prices of apartments on the local secondary housing market. In the article the authors verified the research hypothesis that prices on the secondary housing market are stable in time in given location. They proved it in two ways. Firstly, the linear econometric models with the transaction price as an explained variable and the apartment attributes as explanatory variables were estimated. In the second approach a unit transaction price was transformed into a dichotomous variable and logit models were estimated. Both types of approach were applied in the chosen years of the business cycle on the property market.